A hybrid approach to statutory water law to support smallholder farmer-led irrigation development (FLID) in Sub-Saharan Africa - van Koppen, Barbara; Schreiner, B. (2019)
Millions of small-scale farmers in sub-Saharan Africa who are driving farmer-led irrigation development (FLID) have been turned into criminal offenders or, at least, categorically marginalised under widespread water permit systems. Under these systems, small-scale water users are obliged to apply for a permit, but very few have done so, largely because states lack the administrative capacity to inform such large numbers of people scattered across widespread rural areas with this obligation, to process large numbers of applications and enforce conditions tied to permits. Those who use water below a usually very low threshold, are exempted from this obligation, but small-scale farmers are generally above this category. This viewpoint, based on research and policy dialogues in a range of African countries, elaborates an alternative that addresses these injustices: a hybrid approach to water use authorisation. The proposed hybrid approach provides a suite of tools to legalise the water use of smallholder farmers and to overcome the colonial legacy of the side-lining of customary water law. These tools which can be combined and adjusted to suit specific contexts include: permits, targeted at, and enforced for, the relatively few high-impact users; collective permits; non-permit tools, in particular, first, general authorisations with equal or priority legal standing relative to permits and, second, the recognition of customary water law; and prioritisation.